'Accented' Music Video: Animating Memories of Migration in 'Rocket Man'. Issue 2 (December 2019) - PERROTT, LISA
Abstract : Since its release in 1972, Elton John and Bernie Taupin's song 'Rocket Man' has been treated to a variety of reinterpretations, covers, and performances. But an official music video for this song was not released until 2017. Having been selected as the winner of the music video competition The Cut, Majid Adin teamed up with Stephen McNally to direct an animated video that would become a distinctive visual accompaniment to John's song, while also offering an evocative reimagining of Adin's story of migration during the 2015 refugee crisis. Distinctive for its unusual convergence of genres and its integration of analogue and digital media, this music video offers a rich example of dialogic authorship. Through a close analysis of the sonic, lyrical, and visual construction of 'Rocket Man', this article offers insights into the possibilities for the transformation of music video, specifically in relation to intermedial and artisanal responses to exile and diaspora, and the potential of animated music video to provoke a therapeutic engagement with memory.